Estimation of Immune Response in Rabbits Infected with Attenuated Entamoeba histolytica by Gamma Radation - K. Al-Masoudi, Hayam; H.Al-Sadi, Zainb; Al-Shalaah, Saif A. (Iraqi Journal of Science, 2023)
Out of 1279 stool sample only 245 were found to be infected with E.histolytica with total percentage 19% . Diagnostic study for E.histolytica by using techlab Eliza test showed that the non-pathogen E.dispar was significantly higher (78.9%) than E.histolytica (22%).We test the effect of the attenuated E. histolytica by gamma Radiation on the mortality rate in laboratory animals infected with E. histolytica by using increasing doses of radation (5,10,15,20and 25) Rad., the results showed that the percentage of mortality decrease when increase the dose of attenuated E.histolytica cyst in comparison with positive control group (non – attenuated group) it reached (100% ,66.7%, 33.3% 0% and 0%)respectively. Also we found that gamma radiation elevate some immunological parameters in laboratory animal. So the level of gamma interferon (IFN-γ) reached to (3000pg /ml) and level of ( IgE) reached to (550 mg/L) in comparison to control group ( 130.5 and 78.20 mg/L ) respectively . In conclusion ,the high level (IFN-γ) and (IgE) may be used as indicator for induction of immune responses which may have protective effect against amoebiasis infection.